Protection of Women's Rights Against Cases of Domestic Violence from an Islamic Perspective - A'isy Az-Zahra; Syaifuddin Zuhdi; Ulfah Dwi Rahmawati; Tyas Permata Dewi (Fakultas Syariah, Universitas Islam Negeri Raden Mas Said Surakarta, 2024)
Allah SWT created humans as the most perfect beings and in pairs, instilling affection within the bonds of marriage to achieve the ultimate goal of attaining His pleasure. However, marriage is not without challenges, and one significant issue is domestic violence, where women are often the primary victims. Such occurrences highlight a disregard for women's rights, which are an integral part of human rights. This study aims to explore the position and rights of women as human rights in Islam and examine the legal protections available in cases of domestic violence. Using a normative research method with a statutory approach, this study relies on secondary data collected through literature review and analyzed qualitatively for descriptive presentation. The findings reveal that Islam accords women a high and equal status with men, granting them rights that are fundamental to their humanity. Domestic violence against women is a clear violation of the principles outlined in the Qur'an, As-Sunnah, and Indonesia’s positive law.